2008
DOI: 10.1038/ajh.2008.271
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inflammatory Markers in the Cardioprotective Effect of L-Carnitine in L-NAME-Induced Hypertension

Abstract: The chronic administration of LC reduces blood pressure and attenuates the inflammatory process associated with arterial hypertension. LC might produce a partial inactivation in the RAS resulting in a reduction in the production and effects of angiotensin II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 38 publications
6
47
0
1
Order By: Relevance
“…This indicates that these compounds were able to at least partially ameliorate the inflammatory responses, consistent with previous reports of the anti-inflammatory properties of L-carnitine and betaine. 40,41 It should be noted that among all the compounds, L-carnitine presented the only statistically significant, and the most beneficial effect, on lowering inflammatory responses of all the mediators investigated and demonstrated in both schedules. L-carnitine is essential in maintaining the health of cells 42 and is best known for its important role in the mitochondrial oxidation of long-chain fatty acids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that these compounds were able to at least partially ameliorate the inflammatory responses, consistent with previous reports of the anti-inflammatory properties of L-carnitine and betaine. 40,41 It should be noted that among all the compounds, L-carnitine presented the only statistically significant, and the most beneficial effect, on lowering inflammatory responses of all the mediators investigated and demonstrated in both schedules. L-carnitine is essential in maintaining the health of cells 42 and is best known for its important role in the mitochondrial oxidation of long-chain fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44] Reports further indicate that L-carnitine also possesses anti-inflammatory and immunosuppressive activities. 40,41 An in vivo study using a murine model of Crohn's disease revealed that systemic administration/treatment with L-carnitine during the establishment of colonic inflammation successfully reduced cytokine production and intestinal inflammation, and this protection was associated with a suppressive effect of L-carnitine on the colonic mRNA expression and serum of IL-1b and IL-6. 43 In humans, an immunosuppressive role of L-carnitine is also observed with reduction of TNF-a levels in surgical and AIDS patients after receiving L-carnitine supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, renal and cardiac tubulointerstitial ibrosis takes place and, as a consequence, dysfunction of both organs [60,61]. Concretely, it would be another indicator of universal endothelial functional and structural alteration and of prediction of hypertensive cardiopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Ancak yapılan karnitin desteği prostaglandin I 2 ve nitrik oksit üretimini tekrar artırabilmekte ve ROS üretimini azaltmaktadır. Dahası proinflamatuvar sitokinlerin plazma ve miyokardial ekspresyonunu azaltarak kardiyovasküler hastalıklara karşı koruyucu bir rol oynamaktadır (16,17).…”
Section: Antiaterojenik Etkisiunclassified